Isolation of Candida albicans from some patients who attend hospitals and clinics in the city of Basra in southern Iraq and testing the effect of plant extracts that reduce the growth of these fungi (Texas Journal of Agriculture and Biological Sciences, 2022)
Candida is one of the serious opportunistic fungal pathogens that causes candidiasis. Recently the number of people infected with AIDS worldwide who can contract candida has increased. It is also one of the common fungi that infects humans in the mouth and genitals. Presence of candida in the blood is a serious infection. Candida causes of common infection in blood stream in the USA. Candida fungus was isolated from some patients who visited a number of hospitals in Basra governorate for the purpose of obtaining infected samples. The aim is to know the (antagonistic activity) of extracts of a number of plants as an inhibitor of Candida growth